The role of communication in conflict: A case study at pt. Liek motor - Suliatin (Jurnal Komunikasi Profesional, 2021)
This study focuses on the role of communication in mediating conflict in organizations. Data were obtained by observing and documenting a case on organization conflict that occurred at PT. Liek Motor Indrapura Surabaya. This study is a descriptive qualitative study using Blake & Mouton's theory of conflict management and Thomas & Kilmann's managerial grid theory to understand conflict and its solutions in the organization. The results of the study find that communication serves as the best approach in resolving and mediating conflicts in organizations. Through communication, conflicted parties determine the best solution to mediate their interests. Thus, this study proves that communication can function as the best media in conflict management because it is not only able to mediate and resolve conflicts but also able to prevent other conflicts from occurring in the organization.